La Gran Guerra de las mujeres. El mundo en 1914 y los orígenes del feminismo costarricense - Arias Mora, Dennis (Revista de historia., 2018)
The objective of this article is to determine the effect that the First World War (1914-1918) had on the political, social and cultural spheres of Costa Rican women at the beginning of the 20th century. For this, three types of documentary sources are considered: diplomatic reports, cultural magazines and press. In this way, the article analyzes, first, the study problems contributed by international historiographies of gender and women to the knowledge of the Great War; second, the socio-political overview of Costa Rican women at the time of the war is reconstructed; and third, it analyzes the different repercussions that this war had on women, taking into account the image of women about their participation in the war, their experiences during it as they lived in the country or on the European continent, their forms of distance mobilization and the ways in which this participation affected the shaping of the feminist movement of the time.